Repairing torn webbing - Mumbai Archive Project Team (Jio Institute, 2024)
The strength and efficiency of the structure depend on the integrity of the individual meshes. Repairing torn webbing means retying each knot and restoring the original pattern of the mesh. Generally, the repair twine should have the same diameter and be made from the same material as the netting. The key to good repair is to maintain the integrity of meshes.